Shear properties of a honeycomb structure with zero Poisson”™s ratio (Archives of Mechanics - Test, 2023)
Honeycomb structures with zero Poisson’s ratio show promising potential for application in variable-sweep wing aircraft. The shear properties of these honeycomb structures serve as a crucial indicator of their morphing capacity. This paper derives the linear and non-linear shear properties of a honeycomb structure with zero Poisson’s ratio. A modified factor is introduced to establish a relationship between the linear and non-linear shear modulus of the honeycomb structure, simplifying the calculation method of the non-linear shear modulus. The validity of theoretical predictions is then confirmed using the finite element method Furthermore, the influences of the geometric parameters on the shear properties of the honeycomb structure with zero Poisson’s ratio are investigated, highlighting the varying contributions of these cell geometric parameters to the shear properties.